Quality of life in arthritis patients and its correlation with anxiety and depression - Faisal Siddiqui; N Tripathi (International Journal of Medical Research and Review, 2017)
Background: Although the medical and economic consequences of arthritis are of great concern to researchers and clinicians, this disease also affects an individual’s capacity to live a full and active life.Aim: To study the correlation between depression, anxiety and quality of life among Indian adults suffering from arthritis in a tertiary care centre.Material and Methods: The study sample comprised of adults age above 30 years with clinician diagnosed arthritis (n=370). Depression and anxiety were measured using separate and validated scales. Prevalence was estimated for the sample overall and stratified by subgroups. Associations between correlates and each condition were estimated with prevalence ratios.Result: Depression is significantly negatively correlated to quality of life (r – 0.34 P = 0.0001). Anxiety also negatively correlated to quality of life (r – 0.24 P = 0.0001). Anxiety and depressed patients differed significantly from other arthritic patients in terms of quality of life. (F value 41and P value 0.0001) subjects having both depression and anxiety had the poorest quality of life.Conclusion: Screening for anxiety and depression should form an essential part of the clinical workup of patients suffering from arthritis. Identification of anxiety and depression in subjects suffering from arthritis will have definite implications for comprehensive management of patients.